Evolution of rough-surface geometry and crystalline structures of aligned TiO2 nanotubes for photoelectrochemical water splitting - Zare, Maryam; Solaymani, Shahram; Shafiekhani, Azizollah; Kulesza, Slawomir; Ţălu, Ştefan; Bramowicz, Miroslaw (Scientific reports, 2018)
Nowadays, increasing awareness of environment and fossil fuels protection stimulates intensive research on clean and renewable sources of energy. Production of hydrogen from water through solar-driven splitting reactions is one of the most promising approaches in the field of photoelectrochemistry (PEC). In this work we have fabricated well-aligned, highly-ordered, smooth-mouth TiO 2 nanotube arrays (TNAs) in a two-step anodization process of titanium foil, which were then used as photoelectrodes for PEC water splitting. It demonstrates for the first time correspondence between non-linear component characteristics of multiscale rough surface and crystalline structure of annealed TNAs measured at various fabrication stages and their photoelectrochemical response. The as-anodized TNAs with isotropic surface (deduced from AFM and SEM images) and largest figure of merit (according to their PEC performance) were annealed at 450 °C in air. Scale-invariant descriptors of the surface structure of the deposits involved: fractal dimension, corner frequency, roughness, size of nanostructures and their dominant habits. Moreover, X-ray diffraction data processed using the Rietveld method confirmed co-existence of various oxides, for example: TiO 2 in the form of anatase, TiO and Ti 3 O 5 phases in the TNAs under study pointing that previous well-established mechanisms of the TNA growth were to certain degree incomplete.